Pengaruh Kualitas Produk Terhadap Minat Beli Pakaian Second Import - Jan , Radlyah Hasan; Niu , Fitri Ayu Lestari; Paputungan, Ayu Rosanti; Hasan, Faradila (Forum Kerjasama Pendidikan Tinggi, 2023)
The purpose of the study was to determine the effect of product quality on the interest in buying second-import clothes in students of the Faculty of Economics and Islamic Business IAIN Manado. The research method used in this study is quantitative, data collection techniques using questionnaires distributed through google form then sampling techniques using probability sampling techniques with a total sample of 68 people taken based on the slovin formula then the data is processed using SPSS version 26. Data analysis in this study is simple linear regression. The results obtained a simple linear regression equation, namely Y = 0.643 + 0.494X, this shows that the product quality variable has a positive effect on the variable of buying interest. This is evidenced by the results of the t test where it is known that the calculated t value is 15.256 or greater than the table t value of 1.996 then the value (Sig) is 0.000 or smaller than 0.05. Then in the results of the coefficient of determination test, it is known that the R Square value is 0.779, the value illustrates that the contribution of product quality variables to the buying interest variable is 77.9%. While the remaining 21.1% was influenced by other variants that were not studied in this study. So it can be concluded that there is an influence between the quality of second-import clothing products on the buying interest of students of the Faculty of Economics and Islamic Business IAIN Manado who tend to prioritize dressing styles when doing activities on campus so that in supporting the appearance of using second-imported clothes is one alternative.